Prototheca bovis induces autophagy in bovine mammary epithelial cells via the HIF-1α and AMPKα/ULK1 pathway - Zhao, Wenpeng; Xu, Maolin; Barkema, Herman W.; Xie, Xiaochen; Lin, Yushan; Khan, Sohrab; Kastelic, John P.; Wang, Dong; Deng, Zhaoju; Han, Bo (Frontiers in Immunology, 2022)
Prototheca bovis, a highly contagious pathogen, causes bovine mastitis, resulting in premature culling of affected cows and severe economic losses. Infection with P. bovis caused oxidative stress and apoptosis in bovine mammary epithelial cells (bMECs); however, mechanisms underlying P. bovis-induced autophagy remain unclear. Therefore, the autophagy flux induced by P. bovis in bMECs was analyzed by Western blot and laser scanning confocal microscopy. Expression levels of proteins in the HIF-1α and AMPKα/ULK1 pathway, including HIF-1α, AMPKα, p-AMPKα, ULK1, p-ULK1, mTOR, and p-mTOR, plus expression of autophagy-related genes including SQSTM1/p62, Atg5, Beclin1, and LC3II/LC3I, were quantified with Western blot. Infection with P. bovis induced autophagosomes and LC3 puncta in bMECs that were detected using transmission electron microscopy and laser scanning confocal microscopy, respectively. In addition, lysosome-associated proteins Rab7 and LAMP2a, and lysosomal activity were measured with Western blot and laser scanning confocal microscopy. Infection with P. bovis induced an unobstructed autophagic flux, increased protein expression of LC3II/LC3I, and decreased SQSTM1/p62 protein expression at 6 hpi. Furthermore, P. bovis upregulated protein expression in the HIF-1α and AMPKα/ULK1 pathway and increased the ratio of LC3II/LC3I, implying autophagy was activated in bMECs. However, deletion of AMPKα or ULK1 decreased LC3II/LC3I expression levels and LC3 puncta numbers, suggesting that autophagy was inhibited in bMECs. Additionally, deficiency of HIF-1α decreased protein expression of AMPKα and ULK1 as well as LC3 puncta numbers, and autophagy induced by P. bovis was also inhibited in bMECs. At 6 hpi, lysosome-associated protein Rab7 was decreased and LAMP2a was increased, indicating normal autophagy. In contrast, at 12 hpi, expression of Rab7 and LAMP2a proteins indicated that autophagy was inhibited in bMECs at that time. Therefore, we confirmed that P. bovis infection induced autophagy in bMECs via the HIF-1α and AMPKα/ULK1 pathway, with involvement of lysosome-associated protein Rab7 and LAMP2a.